TERBANGKAN IMAJINASI: MENGURANGI KECANDUAN GADGET PADA ANAK-ANAK DENGAN LAMPION KERTAS - Yeni Nuriati, Junita Fatrila, Winda Sur Yanta Simatupang, Melly Yuliani, Fathia Rebelsha Zahra (CV. ADIBA AISHA AMIRA, 2024)
In the current era of globalization, technology is increasingly sophisticated and developing very quickly, influencing the way humans live, both from a cognitive and action perspective. As part of technological advances, gadgets have become contemporary communication tools that greatly influence everyday life. In the last two years, the use of these devices has increased rapidly in Indonesia. Gadgets are increasingly in demand, especially by children because of the easy access to information and entertainment they offer. However, excessive use of gadgets can interfere with intelligence, especially in children who are introduced to gadgets at an early age. The aim of this research is to overcome electronic device addiction in children through the use of art activities such as folding paper lanterns. This research used a pre-experimental design, one group pre-test-post-test. This allows comparison of conditions before and after treatment. The research subjects were ten students of Kindergarten Kartika 157 Bukittinggi, who were selected using a saturated sampling technique.